2003
DOI: 10.2298/avb0304219s
|View full text |Cite
|
Sign up to set email alerts
|

The serum levels of insulin and igf-i in newborn piglets treated with clinoptilolite

Abstract: The aim of this study was to investigate the influence of the natural mineral adsorber clinoptilolite on the serum levels of insulin and insulin-like growth factor-I in newborn piglets in the first 30 hours postnatally. A total number of 40 crossbred Landrace x Duroc newborn piglets from 4 litters was used. Five piglets from each litter were randomly assigned to the treated group and another five piglets to the control group. The treated animals received 10 ml of 15% clinoptilolite suspension three times: imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…et al showed a positive relationship between ALP and blood sugar, 34 thus higher levels of ALP among diabetic groups than NC were expected in the current study. The additive effect of CLN on higher levels of insulins 35 was expected to decrease glucose levels in the diabetic-control group more than the normal-control.…”
Section: Discussionmentioning
confidence: 99%
“…et al showed a positive relationship between ALP and blood sugar, 34 thus higher levels of ALP among diabetic groups than NC were expected in the current study. The additive effect of CLN on higher levels of insulins 35 was expected to decrease glucose levels in the diabetic-control group more than the normal-control.…”
Section: Discussionmentioning
confidence: 99%